PERENCANAAN TEKNIS OPERASI PRODUKSI BIJIH TIMAH DI BLOK 3 TAMBANG BESAR 2.1 MITRA PT TIMAH (PERSERO) TBK - Awwab Hafizh; E.P.S.B Taman Tono; Anisa Indriawati (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2017)
The process of tin ore mining in TB 2.1 is conducted by channeling slurry (the mixture of ore and water) from the stock pile into the washing unit by using slurry pump. Now, TB 2.1 is planning block 3 for the operation of tin ore production proceess. Thus, a good technical planning in accordance with the characteristic of tin ore in TB 2.1 and evaluation of operating system design in Block 1 are necessary. The sample of tin ore concentrate is taken as many as 250 gr from the washing unit to detect P80 of particle size distribution (PSD) of sample. The data of sucker and pressure pipe’s lenghth, store tank’s height, quantity of primary and secondary jig and tin ore monthly production are required to furthermore plan the mining design, washing plant and equipment needs in the drying unit. Based on the research findings, It is obtained the grain size distribution of tin ore is 1.001 mm, so that the amount of lifting velocity is 3.27 m/s. Slurry pump discharge with a pipe’s diameter of 10 inches is 54 m3/hour, while total head of mining design is 30.23 m. Width of launder required is 6.5 m and equipped with two Grizzlies. Washing plant requires three units of primary Jig (2 × 3 cell) and a unit of secondary jig (2 × 3 cell). Adding rotary vibrating screen, shaking table and rod mill are necessary for process optimization in the drying unit.